In Kenya’s Nandi county, stakeholders jointly reflect on a theory of change for low-emission food systems transformation - Falk, Thomas; Walter, Kibet; Habermann, Birgit (CGIAR Initiative on Low-Emission Food Systems, 2023)
Food system transformation requires efforts from diverse stakeholders. It involves clarifying roles and relationships, as well as mobilizing and connecting them.